2002
DOI: 10.1007/s00405-001-0428-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic work-up of socially unacceptable snoring

Abstract: In the diagnostic work-up of socially unacceptable snoring (SUS) with or without a history suggestive of obstructive sleep apnoea syndrome (OSAS), information on the severity of the pathology as well as on local and general causative factors is needed. In part I of this study, we reported on the findings recorded in 380 patients by means of sleep registration. In this part, our emphasis is on analysis of the local contributing factors. In 340 of the 380 patients sleep endoscopy was performed to establish the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…The database is strongly imbalanced with a comparatively low number of T and E samples. This is consistent with earlier medical research, which has found that respiratory disturbances occur more frequently at velopharyngeal and oropharyngeal level, compared to the hypopharyngeal level [50]. For more specific information about the database, the readers are referred to [10].…”
Section: Training and Validationsupporting
confidence: 89%
“…The database is strongly imbalanced with a comparatively low number of T and E samples. This is consistent with earlier medical research, which has found that respiratory disturbances occur more frequently at velopharyngeal and oropharyngeal level, compared to the hypopharyngeal level [50]. For more specific information about the database, the readers are referred to [10].…”
Section: Training and Validationsupporting
confidence: 89%
“…21 Various articles have described respective sedation methods, but there is no standardized protocol. [4][5][6][7][8]22 The ideal concentration differs per individual, depending on his or her susceptibility to the sedative effect of the drug. Slow stepwise induction is vital to avoid oversedation, yielding falsepositive results.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 DISE, performed for decades in many leading centers in Europe as well as in selected centers in other parts of the world, is indicated when surgery or oral device therapy is being considered as a treatment option by the patient and physician. [5][6][7] Before DISE, polysomnography (PSG) must be performed to assess the severity of the OSA. The PSG results are compulsory and at the basis of performing DISE.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomic narrowing of the upper airways is considered one of the reasons for patients developing SRBD. Still, surgical treatment for opening up the obstructed area has not gained popularity, mainly because of the poor outcomes 7 and undesirable side effects, including postoperative pain, scarring, fibrosis, and mouth dryness. 11 With the CAUP procedure, no such negative effects were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing surgical outcomes within the SRBD population requires properly identifying the site of partial or total pharyngeal obstruction during sleep as well as using a surgical tool allowing for site-specific surgery. 7 To target the optimal surgical site in SRBD patients, we have used a system consisting of micropressure transducers mounted in a thin, soft, and flexible polyurethane catheter (Apnea-Graph, MRA-Medical Ltd, Gloucestershire, UK) for several years to measure pressure gradients in the upper airway and esophagus and to collect polygraphy information during sleep. We recently began using bipolar plasmamediated radiofrequency-based (coblation) instruments to perform UPPP procedures, allowing for treatment under local anesthesia on an outpatient basis.…”
Section: Introductionmentioning
confidence: 99%